2003
DOI: 10.1007/bf02704456
|View full text |Cite
|
Sign up to set email alerts
|

The quark gluon plasma: Lattice computations put to experimental test

Abstract: Abstract. I describe how lattice computations are being used to extract experimentally relevant features of the quark gluon plasma. I deal specifically with relaxation times, photon emissivity, strangeness yields, event by event fluctuations of conserved quantities and hydrodynamic flow. Finally I give evidence that the plasma is liquid-like rather in some ways.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The advantage is that the formalism of Section II B can be used to compute second derivatives of the free energy as operator expectation values. If the EOS were to be evaluated by the "integral" method, then these quantities could only be evaluated by numerical differentiation [23], which is a less attractive solution.…”
Section: On the Methodsmentioning
confidence: 99%
“…The advantage is that the formalism of Section II B can be used to compute second derivatives of the free energy as operator expectation values. If the EOS were to be evaluated by the "integral" method, then these quantities could only be evaluated by numerical differentiation [23], which is a less attractive solution.…”
Section: On the Methodsmentioning
confidence: 99%
“…This new form of matter is thought to be a fluid of strongly interacting quarks and gluons. In lattice studies of quenched QCD it was found earlier that the entropy density s [2,3] and the mean free time τ , derived from the electrical conductivity [4], together gave rise to a dimensionless number τ s 1/3 ≈ 0.8 [5]. In the non-relativistic limit this dimensionless number measures the mean free path in units of interparticle spacing, and is therefore large in a gas but of order unity in a liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensionally, τ π = a/T , where a is dimensionless, and becomes constant when the fluid has conformal symmetry. This dimensionless number is proportional to the quantity called liquidity [28] which, in non-relativistic fluids, measures the mean-free path (proportional to τ π ) in units of the interparticle spacing (proportional to 1/s 1/3 ∼ 1/T ). In a gas, this number is very large, in liquids, small.…”
Section: A Materials Properties At Vanishing Chemical Potentialmentioning
confidence: 99%